The Leading Eikonal of the Scattering Amplitude of Particles in Gravitational Field at High Energy Using the Partial Wave Method - Nguyen, Suan Han (H. : ĐHQGHN, 2017)
The scattering amplitudes for two spineless particles colliding at Planckian center-of-mass energies are considered by the partial wave method in quantum gravity. In the framework of the partial method, a scheme for finding the leading eikonal scattering amplitudes is developed and constructed. The connection between the solutions obtained by partial wave method, quasi-potential and functional approaches is also discussed.